Social Support in Massive Open Online Courses: A Literature Review - et.al, Buyut,V.C (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Massive Open Online Courses (MOOCs) provide quality higher education resourcesfor people around the world. It allows massive number of learners to gain access to free, virtual based open educational subjects offered by accredited and world recognized top ranking institutional. However, numerous studies show that MOOCs success was marred by low completion and high dropout rates.This studyintends to identify and analyse the literature on the social support related factors influencing the utilization of MOOCs. Results from the review show that the relevant and related researchesare extremely limited which call for further studies to be done on influence of social support on MOOCs usage. The review reveals that emotional support is the most identified social support factor included in MOOC studies from various perspectives followed by informational support. Tangible support and belonging support are the least to be included in the selected studies. This review reveals that more researches are required to identify the impact of social support factors in influencing the utilization of MOOCs among learners.